PENGARUH EFEKTIVITAS DAN EFISIENSI PENGELOLAAN KEUANGAN DAERAH SERTA SISTEM PENGENDALIAN INTERN TERHADAP KEANDALAN LAPORAN KEUANGAN PEMERINTAH DAERAH - Suhendro, Saring (Jurnal Akuntansi dan Keuangan (JAK), 2024)
The research aims to obtain empirical evidence that the effectiveness and efficiency of local financial management, as well as the internal control system of local governments, influence the reliability of local government financial reports. This research utilizes secondary data in the form of financial reports from districts/cities throughout Indonesia, with a total population and sample size of 524 district/city governments. The data used is cross-sectional data for the year 2022. The results of the testing indicate that the effectiveness of local financial management has a significant positive effect on the reliability of local government financial reports, and the internal control system measured by weaknesses in the internal control system has a significant negative effect on the reliability of local government financial reports. However, efficiency does not have a significant effect on the reliability of local government financial reports.